"As Closely Bonded as We are:" Animalographies, Kinship, and Conflict in Ceridwen Dovey's Only the Animals and Eva Hornung's Dog Boy. (2nd January 2020) - Moore, Grace
Abstract: Using the fiction of Ceridwen Dovey and Eva Hornung, this essay considers animalography as a medium to represent animal emotions, particularly when ties of kinship break down. It addresses the difficulties and power dynamics associated with speaking for nonhuman others, while engaging with Cynthia Huff's cautions regarding the posthumanist life narrative.